GMAT Question of the Day - Daily to your Mailbox; hard ones only

 It is currently 22 Feb 2019, 11:09

### GMAT Club Daily Prep

#### Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

## Events & Promotions

###### Events & Promotions in February
PrevNext
SuMoTuWeThFrSa
272829303112
3456789
10111213141516
17181920212223
242526272812
Open Detailed Calendar
• ### Free GMAT RC Webinar

February 23, 2019

February 23, 2019

07:00 AM PST

09:00 AM PST

Learn reading strategies that can help even non-voracious reader to master GMAT RC. Saturday, February 23rd at 7 AM PT
• ### FREE Quant Workshop by e-GMAT!

February 24, 2019

February 24, 2019

07:00 AM PST

09:00 AM PST

Get personalized insights on how to achieve your Target Quant Score.

# If (3/y + 2)(y - 5) and y ≠ 5, then y =

Author Message
TAGS:

### Hide Tags

Math Expert
Joined: 02 Sep 2009
Posts: 53066
If (3/y + 2)(y - 5) and y ≠ 5, then y =  [#permalink]

### Show Tags

11 Feb 2019, 23:28
00:00

Difficulty:

15% (low)

Question Stats:

89% (01:19) correct 11% (01:28) wrong based on 18 sessions

### HideShow timer Statistics

If $$(\frac{3}{y} + 2)(y - 5)=0$$ and y ≠ 5, then y =

(A) -3/2
(B) -2/3
(C) 2/3
(D) 3/2
(E) 6

_________________
VP
Joined: 31 Oct 2013
Posts: 1162
Concentration: Accounting, Finance
GPA: 3.68
WE: Analyst (Accounting)
Re: If (3/y + 2)(y - 5) and y ≠ 5, then y =  [#permalink]

### Show Tags

11 Feb 2019, 23:35
1
Bunuel wrote:
If $$(\frac{3}{y} + 2)(y - 5)=0$$ and y ≠ 5, then y =

(A) -3/2
(B) -2/3
(C) 2/3
(D) 3/2
(E) 6

y can't be 5.

( y - 5) = 0

y = 5.

we must ignore this value.

(3/y + 2 )

$$\frac{3 + 2y}{y}$$ =0

3 + 2y = 0

2y = -3

y = -$$\frac{3}{2}$$

VP
Joined: 09 Mar 2018
Posts: 1002
Location: India
Re: If (3/y + 2)(y - 5) and y ≠ 5, then y =  [#permalink]

### Show Tags

11 Feb 2019, 23:39
Bunuel wrote:
If $$(\frac{3}{y} + 2)(y - 5)=0$$ and y ≠ 5, then y =

(A) -3/2
(B) -2/3
(C) 2/3
(D) 3/2
(E) 6

now if y != 5

we can equate the previous expression to 0

3/ y = -2

y =-3/2

A
_________________

If you notice any discrepancy in my reasoning, please let me know. Lets improve together.

Quote which i can relate to.
Many of life's failures happen with people who do not realize how close they were to success when they gave up.

Re: If (3/y + 2)(y - 5) and y ≠ 5, then y =   [#permalink] 11 Feb 2019, 23:39
Display posts from previous: Sort by